A PRISMA-based Thematic Analysis of Smart City Maturity Models: Mapping Key Dimensions and Maturity Levels - Widya Listianingsih; Tony Dwi Susanto (Journal of Information System Research (JOSH), 2025)
In the era of rapid urbanization and the increasing demand for sustainable urban development, smart cities have emerged as a critical focus for enhancing the quality of urban life. However, existing smart city maturity models lack standardization, making it challenging for cities to evaluate their progress comprehensively. This study addresses these challenges by identifying and analyzing the key dimensions and maturity levels across 11 smart city maturity models. Using a systematic literature review guided by the PRISMA approach and thematic analysis, this research uncovered significant insights. Eight key dimensions were identified, with the smart environment dimension appearing in 10 models, highlighting its centrality in addressing environmental and sustainability issues. Smart governance and smart society were also frequently highlighted, emphasizing their critical roles in fostering effective urban management and promoting social inclusion in smart city development. Additionally, 8 models employed a five-level maturity structure, demonstrating its widespread acceptance for balancing detail and simplicity in assessing a city's growth. These findings provide cities with a structured framework to evaluate and enhance their smart city strategies while facilitating comparisons among existing models. The results emphasize the need for a standardized yet flexible approach to smart city maturity, enabling cities to navigate their unique challenges effectively and achieve sustainable growth.